STRATEGI PENINGKATAN KETAHANAN PANGAN DI KABUPATEN SITUBONDO - Lia Ristina; i Wayan Subagiarta; Anifatul Hanim (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2014)
Food endurance is the main priority in the development. Situbondo District is one of horseshoe areas where the food shortages were rarely happening. Thus, it is necessary to improve food endurance in Situbondo District. This study was aimed to find out the external and internal factors influencing the improvement of food endurance in Situbondo District and to investigate the strategies to improve food endurance in Situbondo District. This was observational research study employing descriptive analysis technique, as well as, using SWOT analysis to formulate the strategies to improve food endurance n Situbondo District. The sampling technique was done by purposive sampling. The data were collected both from three key informants and related institutions. Then, the data were proceed and analyzed  through three steps which were evaluation of external factor, evaluation of internal factor, and SWOT analysis. The findings showed that: 1) The analysis of external and internal factors was on the quadrant of II with its recommended strategy was diversification strategy (it was located in the right position but it still faced various obstacles coming from external environment), 2) Some f the strategies were improving human resources of governmental apparatus in supporting the technology application of local food process; constructing several integrated food policies together with the local government as the main role in an effort to control the price of main needs, as well as the other conditions influencing the instability of the three sub-systems of food endurance; and embracing the organizations supporting the socialization of the technology of local food development. Keywords: strategy, food endurance, Situbondo District